Polyarthritis in a Dog Due to Leishmaniasis - Treatment with Miltefosine - Castilhano Marcelino Silva, André; Prestes Conceição, Ana Flávia; Caramalac, Silvana Marques; Marques Caramalac, Simone; Coltro Gazzone, Alexandre; Antonio Terrabuio Andreussi, Paulo; Isa Poci Palumbo, Mariana (Acta Scientiae Veterinariae, 2023)
Background: Canine visceral leishmaniasis causes several clinical signs, such as lymphadenomegaly, exfoliative dermatitis, ulcerative skin lesions, and lameness. The most commonly reported locomotor changes are claudication, edema, arthralgia, joint stiffness, and muscle atrophy. Radiographic exam revealed cortical and medullary destruction, increase, or decrease in medullary opacity, proliferative periosteal reaction, osteolysis, collapse of joint spaces and soft tissue edema are observed. The aim of this report is to describe the clinical and radiographic evolution of a case of erosive polyarthritis associated with leishmaniasis in a dog before, during and after treatment with miltefosine. Case: A 7-month-old mixed-breed dog was attended due pain and limited mobility. In the orthopedic evaluation, joint swelling, stiffness, and increased pain sensitivity of the four limbs, as well as neck stiffness, were noted. Radiographic examination showed joint changes compatible with edema, with increased volume and radiopacity of the soft tissues adjacent to the joints. The segments of the patient's spine showed more severe bone alterations, the cervical spine being one of the most affected regions, with multiple bone proliferations throughout the vertebral body, especially in the ventral portion (spondylosis), compatible with polyarthritis due to leishmaniasis. Due to the suspicion, lymph node and spleen cytology was performed, confirming the diagnosis. Hematological examination revealed anemia, leukopenia due to lymphopenia and thrombocytopenia in addition to increased AST (79,4 U/L; reference: 6,2 - 13 U/L), creatine kinase (517,6 U/L; reference: 1,5 - 28,4 U/L), lactate dehydrogenase (688,4 IU/L; reference: 45 - 233 IU/L) and hyperproteinemia (7,34 g/dL; reference: 5,4 - 7,1 g/dL). Treatment with miltefosine, allopurinol, domperidone, prednisone, gabapentin and dipyrone was started. Reassessments were performed monthly for 3 consecutive months. Hematological examinations showed improvement, with resolution of anemia and thrombocytopenia, and a marked decrease in creatine kinase values. Thus, it is evident that the dog did not develop liver or kidney changes during treatment. During the treatment and monitoring in this period, the dog had a clinical improvement, which started to walk without pain. In addition, joint swellings were no longer present, however, there was no improvement in the radiographic evaluation of the joints. Discussion: Clinical signs of the locomotor system are compatible with those described in animals that had osteoarticular manifestations associated with leishmaniasis, such as arthralgia, edema, and joint stiffness. In the present report, treatment with miltefosine associated with allopurinol resulted in an improvement in the clinical picture, and this therapy is therefore promising in dogs with polyarthritis due to leishmaniasis. A case published in human medicine demonstrated the intra-articular absorption capacity of this drug. There is only one study to date that describes the radiographic evolution of a dog with arthritis due to leishmaniasis after treatment with miltefosine and allopurinol. In this case described, the dog reported remained with the osteoarticular lesions after treatment, although clinical improvement was observed, as in our report. The use of miltefosine and allopurinol are in accordance with stage II staging for leishmaniasis. In this study, although there was no improvement in the radiographic examinations, the treatment was effective in the remission of the animal's clinical condition. Keywords: allopurinol, amastigotes, domperidone, joint, leishmanicide. Título: Poliartrite em cão por Leishmaniose - tratamento com miltefosina. Descritores: alopurinol, amastigotas, articulação, domperidona, leishmanicida.